Saving of Foot Support Ability in Post-traumatic Defects Using Microsurgical Tissue Autotransplantation - A. P. Vlasov; E. Y. Shibayev; A. M. Fayn; P. A. Ivanov; D. A. Kisel; M. P. Lazarev; K. V. Svetlov; A. V. Nevedrov (Неотложная медицинская помощь, 2020)
Background. Severe open injuries of the lower extremities in most cases are the result of high-energy trauma, because the foot and ankle are damaged as a result of automobile accidents almost in every fourth victim. According to the literature, the percentage of infectious complications after surgical debridement of open injuries of the foot is 43–67.9% and shows no tendency to decrease.Material and methods. We performed 32 operations with the use of free revascularized grafts in patients aged from 16 to 70 years with extensive posttraumatic defects of the foot between 2010 and 2018.Results. As a result, 30 (93.7%) out of 32 grafts provided foot support ability provided during the post-operative period. When replacing large defects (more than 80 cm2) of soft tissues supporting surface of the foot we used free musculocutaneous flap of the latissimus dorsi, fasciocutaneous flaps were used for defects of the dorsum of the foot (less than 80 cm2). Long-term results were assessed using the Foot and ankle ability Measure (FAAM) questionnaire.Conclusion. Primary early replacement of tissue defects on the foot with free revascularized autografts is the method of choice for solving this problem, as it allows you to maintain the supporting function of the foot and is often alternative method to amputation.